Preoperative state anxiety predicts postoperative health-related quality of life: A prospective observational study on patients undergoing lung cancer surgery - Takamiya, Shinnosuke; Honma, Motoyasu; Masaoka, Yuri; Okada, Momoka; Ohashi, Shinichi; Tanaka, Yoko; Suzuki, Kosuke; Uematsu, Shugo; Kitami, Akihiko; Izumizaki, Masahiko (Frontiers in Psychology, 2023)
Objective Improving quality of life (QOL) after surgery is very important. Recently, preoperative anxiety has been suggested to predict postoperative health-related (HR) QOL, however the accuracy of anxiety measurement remains problematic. We examined the relationship between preoperative anxiety level and postoperative HRQOL using qualitative and quantitative assessment of anxiety. Method We used a detailed anxiety assessment to quantitatively investigate preoperative anxiety as a predictor of postoperative HRQOL in lung cancer patients. Fifty one patients who underwent surgery for lung cancer were included. They were assessed four times: on admission, on discharge, 1 month after surgery, and 3 months after surgery. Anxiety was measured separately as “state anxiety” and “trait anxiety” using the State–Trait Anxiety Inventory, and HRQOL was measured using the EuroQol 5 dimension 5-level. Results The HRQOL decreased at discharge and gradually recovered over time, reaching the same level at 3 months after surgery as at admission. HRQOL score was lower at discharge than at pre-surgery and 3 months after the surgery (p < 0.0001 each), and the score at 1 month after the surgery was lower than at pre-surgery (p = 0.007). In addition, multiple regression analysis showed that HRQOL at discharge was associated with “state anxiety” rather than “trait anxiety” at admission (p = 0.004). Conclusion This study identifies the types of anxiety that affect postoperative HRQOL. We suggest that postoperative HRQOL on discharge may be improved by interventions such as psychological or medication treatment for preoperative state anxiety if identified preoperative state anxiety can be managed appropriately.